Action vs Enaction: The 15-M and its Reverberation in the City - García-Hípola, Mayka; Beltrán Rodríguez, María (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2013)
This article seeks to analyze the relationship between public space –the physical– and civic action –the social–. It uses the 15-M Movement as a case study, framed within the global occupation movement. It will examine the self-organization and the use of new technologies and their potential for citizens’ action and transformation of public space, as well as the phenomenon of occupation and empowerment. How public is public space? The research focuses on the two opposing actors involved in public space: the legal and regulated (current planning system) and the spontaneous and often illegal (social movements). The conclusions lead towards ways to achieve a balance between the design of a public space as a place for representation and for action, as both an insurgent and institutional space, halfway between a rigid and regulated design and a flexible and spontaneous one.